A Network Pharmacology Identified Metastasis Target for Oral Squamous Cell Carcinoma Originating from Breast Cancer with a Potential Inhibitor from F. sargassaceae - Abdullah Alqarni; Jagadish Hosmani; Saeed Alassiri; Ali Mosfer A. Alqahtani; Hassan Ahmed Assiri (MDPI AG, 2024)
This study aimed to identify specific therapeutic targets for oral squamous cell carcinoma (OSCC) that metastasize from breast cancer (BC) by using network pharmacology. The Gene Expression Omnibus for OSCC and BC served as the source of gene expression datasets and their analysis. Upregulated genes and the common intersecting genes of these cancers were determined along with that of the phytochemicals of F. sargassum to predict the pharmacological targets. Further, gene enrichment analysis revealed that their metastasis signature and metastasis targets were determined via a protein interaction network. Molecular docking and pharmacokinetic screening determined the potential therapeutic phytochemicals against the targets. The interaction network of 39 genes thus identified encoding proteins revealed HIF1A as a prominent metastasis target due to its high degree of connectivity and its involvement in cancer-related pathways. Molecular docking showed a strong binding affinity of isonahocol D2, a sargassum-derived compound with HIF1A, presenting a binding energy of −7.1 kcal/mol. Further, pharmacokinetic screening showed favorable ADME properties and molecular dynamics simulations showed stable interactions between isonahocol D2 and HIF1A, with significant stability over 100 ns. This study's results emphasized that isonahocol D2 is a promising therapeutic candidate against HIF1A in OSCC metastasized from breast cancer in translational medicine.